Attitude towards information property rights among students : The case of International Islamic University Malaysia - Mohamud, Ibrahim Kalif; Saidin, Aznan Zuhid; Akram, M. Zeki (IEEE, 2017)
Information Property issues are among the criteria of Computer ethics associated with the advent of Internet. New ethical issues are raising continuously due to the fast development of Information & Communication Technology I.C.T but ethical issues related with using I.C.T are unclear to most of the students. This research explores the attitude of the participants (students) of International Islamic University Malaysia (I.I.U.M) to the issues related to Information Property and studies the differences existence of characteristics of students such as age, level of study, gender, marital status, and computer usage regarding their attitudes with information Property issues. A total of 219 participants were questioned from postgraduate and undergraduate levels of I.I.U.M in Gombak campus. The analysis shows that most students were insensitive to the ethicality of information property and software copyright compliance. No significant changes between individual characteristics were found regarding students’ attitude towards computer ethics and property. It is suggested that up to date ethics education courses taught from an Islamic perspective as part of curricula of the university can contribute students’ positive attitude to information property.